President Trump’s prescription to reduce drug prices: from the campaign trail to American Patients First - Dabbous, Monique (J Mark Access Health Policy, 2019)
Background: Drug prices in the United States are the highest in the world, restricting access to the domestic lower income population. President Trump campaigned heavily on promises to reduce drug prices.Methods: A literature review was conducted through PUBMED, EMBASE, Media and grey literature to consolidate and analyze publications addressing President Trump’s promises from the campaign trail as well as the shortcomings and achievements of the Trump administration.Results: Major promises ranged from repealing and replacing Obamacare, expanding coverage, allowing cross-state insurance purchasing, and reducing drug prices. Main accomplishments of the Trump administration have been two executive orders (13765 and 13813), the proposition of the American Health Care Act, and the passing of the Tax Cuts and Jobs Act of 2017. The American Patients First blueprint further revealed the administration’s strategies for lowering drug prices. The administration has also engaged in unconventional strategies, such as via bilateral leverage directly with trade partners.Conclusion: The Trump administration has not yet been able to fulfill the major campaign promises, primarily the ones requiring legislative and/or administrative action. If enough legislative action is accomplished to implement the Trump administration’s promises, the effects on the pharmaceutical industry could be direct, yet minimal, unless Medicare can directly negotiate with manufacturers.